Disclosure of Wood Processing Industry Sustainability: Economic, Social, or Environment? - Ajeng Ayu Selva Mutiara Dewi (AIBPM Publisher, 2022)
ABSTRACT Every activity of the companies has its own impact both for the companies and the surrounding environment. In this case, the companies are expected to be capable to properly implement corporate social responsibility to minimize the negative impact of their activities. This research was conducted to know the sustainability disclosures carried out by the companies on aspects of raw materials, biological diversity, wastewater, waste, as well as compliance with economic, social, and environmental aspects in accordance with the 2016 GRI Standards. This study applies a qualitative approach method with content analysis in which within its implementation is based on a statement according to certain criteria and is classified through keywords. The results of the study indicate that all observed companies have carried out disclosures based on the 2016 GRI Standards, although they are so undetailed and there are still several key words in aspects that have been unsubmitted by all the observed companies. Keywords: Disclosure, Sustainability, Economic, Social, Environment